Use of a molecular tracking system to study the survival and migration of Pseudomonas putida, a biocontrol agent for sheath blight disease of rice - S.S. GNANAMANICKAM, S. MAGESWARI and (Indian Phytopathology, 2002)
The lacZY genes were inserted into P. putida Vl4i which is a biocontrol agent for sheath blight disease of rice caused by Rhizoctonia solani. The marked strain, P. putida Vl4i-gal had blue coloured colonies which aided in easy detection of the presence of the bacterium in rice seed, root or leaf tissues. In a greenhouse experiment it was observed that the marked strain persisted in IR50 rice roots for 60 d in sterile soil or for 50 d in nonsterile soil after the seeds were coated with the bacterium. It migrated to rice seedlings only for 10 d after seedling emergence. The bacterium survived in rice foliage for 40 d after it was applied as a foliar spray application. The wild-type and the marked P. putida Vl4i strains afforded 61-62% sheath blight suppression in IR50 rice.